Hydrochemical characteristics and exchange dynamics between surface water and groundwater in an arid river basin - Xiao, Yi; Ren, Cai; Zhang, Ji; Huo, Jianyu; Zhang, Yanfei; Wang, Wenjun; Chen, Haojie; Yu, Jiawen; Long, Aihua (Frontiers in Earth Science, 2026)
The Weigan River Basin, located in the arid region of northwest China, faces severe water scarcity. The complex interactions between surface water and groundwater pose a critical challenge for accurately assessing total water resources. To elucidate the exchange mechanisms and fluxes, this study employs a comprehensive analytical approach integrating hydrochemistry, stable isotopes (δ18O, δD), and Bayesian mixing models (MixSIAR). Hydrochemical analysis reveals a patterned spatial evolution of water chemistry characteristics within the basin. Mountainous surface waters predominantly exhibit a HCO3·SO4-Ca·Mg type, controlled by the weathering of carbonate and silicate rocks. Groundwater chemistry evolves along the flow path from an HCO3·Cl-Na·Ca type to an HCO3·SO4-Na·Ca type, revealing groundwater recharge from surface water rich in SO42-. In the plains, groundwater undergoes further evaporation and concentration, cation exchange adsorption, and human activities, eventually discharging into surface water and causing elevated Na+ levels in rivers. Based on these insights, MixSIAR model quantification reveals a clear and statistically significant spatiotemporal transformation pattern. In mountainous sections (Heizi River, Karasu River, Tairweichuk River, upper reaches of both the Muzhati River and Weigan River), surface water serves as the primary groundwater recharge source (dry period contribution: 59%–70%; wet period contribution: 54%–59%). Conversely, in the plain areas of the lower reaches of both the Muzhati and Weigan Rivers, groundwater replenishes surface water (dry period contribution: 53%–55%; wet period contribution: 56%–63%). Seasonally, surface water contribution during the dry period is on average 7.6% higher than during the wet period. In contrast, groundwater contribution in the plain region is on average 5.5% higher during the wet period than during the dry period. Through a research approach combining geochemical tracing and quantitative modeling, this study not only reveals the water cycle patterns in the Weigan River basin but also provides quantifiable scientific basis for precise simulation and management of water resources in arid inland river basins.